2020
DOI: 10.1002/cbdv.201900552
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Insecticidal Activity of Crithmum Maritimum L. Essential Oil against Stored‐Product Beetle Tribolium Castaneum

Abstract: Several plant essential oils have been used against diverse insect pests since, unlike conventional pesticides, they pose almost no risk to humans and the environment. For this reason, the essential oil (EO) isolated from the fresh leaves of Crithmum maritimum L. and its fractions (F1–F5) obtained by chromatographic simplification were investigated for their chemical profile, as well as for their toxicity and repellency effects against Tribolium castaneum (Herbst) adults. The analysis by GC/MS allowed the iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 67 publications
(111 reference statements)
0
15
0
1
Order By: Relevance
“…Apiole and methylthymol are in correspondence with dill-apiole (an isomer of apiole) and thymol methyl ether, two of the major components of C. maritimum essential oil from Kélibia and Monestir reported by Jallali, et al [30]. Dill-apiole was also referred by Ngom, et al [43], Houta, et al [9], and Ben Mustapha, et al [44]; and thymol methyl eter by Alves-Silva, et al [45] and Nabet, et al [10]. The main difference between the composition of our extracts and those reported by some authors [9,10,46] is the absence of γ-terpinene and sabinene in the extracts presented herein.…”
Section: Active Components By Gc-ms Analysismentioning
confidence: 73%
“…Apiole and methylthymol are in correspondence with dill-apiole (an isomer of apiole) and thymol methyl ether, two of the major components of C. maritimum essential oil from Kélibia and Monestir reported by Jallali, et al [30]. Dill-apiole was also referred by Ngom, et al [43], Houta, et al [9], and Ben Mustapha, et al [44]; and thymol methyl eter by Alves-Silva, et al [45] and Nabet, et al [10]. The main difference between the composition of our extracts and those reported by some authors [9,10,46] is the absence of γ-terpinene and sabinene in the extracts presented herein.…”
Section: Active Components By Gc-ms Analysismentioning
confidence: 73%
“…The aerial parts of the species contain a great diversity of volatile compounds, including sabinene, α-Terpinene, γ-Terpinene, limonene, terpinen-4-ol, thymyl methyl oxide, p-Cymene, α-Pinene, Z-β-Ocimene, β-Phellandrene, dillapiole and myrcene [1,7,21,23,[82][83][84][85][86].…”
Section: Chemical Compositionmentioning
confidence: 99%
“…In addition to the above properties, sea fennel exhibits a considerable insecticidal activity against serious pests of crops and insects of health importance such as the red flour beetle (Tribolium castaneum Herbst. ), the cotton leafworm (Spodoptera litura F.), the yellow fever mosquito (Aedes aegypti L.) and the southern house mosquito (Culex quinquefasciatus Say) [18,20,21]. In particular, Mustapha et al [21] observed that the essential oil obtained from the fresh leaves of sea fennel exhibited both repellent and toxic effects against the adults of the red flour beetle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the use of plant extracts such as essential oils has been a promising natural methodology [4] . The essential oils can also be applied as repellents or insecticides for treatment of stored products [5–8] . These are effective ecological alternatives to synthetic pesticides [5] .…”
Section: Introductionmentioning
confidence: 99%